Level of Professional Competence of State Madrasah Ibtidaiyah (MIN) Teachers in Palembang City - Ahmad Zainuri; Miftachul Huda; Febriyanti Febriyanti (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2021)
This study holds to answer of how the level of professional competence of teachers in the State Madrasah Ibtidaiyah (MIN) Palembang City. It is expected to be beneficial as study materials for the managers and other stakeholders. The type of this research is field research with the State Madrasah Ibtidaiyah (MIN) teachers’ population of Palembang City amounted to 85 teachers. The writer collected the data through questionnaires, interviews, observation, and documentation study and analyzed using a descriptive statistical technique. The assessment is done by the Likert scale. The data analysis describes how much teachers' level of competence. The descriptions and categorization of data used the guidelines of tabulation data considering the minimum, maximum, interval index values, and distance intervals. The minimum index value is the minimum score multiplied by the number of questions multiplied by the number of respondents; the maximum value is the highest score times the number of questions multiplied by the number of respondents; the interval index value is the difference between the maximum index value and the minimum index value, and the distance interval is the interval divided by the desired number of levels. This study found that the professional competence of MIN teachers in Palembang city in the category was enough (average score 281.98). The only dimension of professional competence was in a good category is to utilize information and communication technologies to communicate and self-development. Meanwhile, other professional competencies: (a) mastering the materials, structures, concepts, and scientific mindsets support the subjects that are taught; (b) mastering the competency standard and basic competency of the subject/field of development that is supported; (c) developing creatively-taught learning materials; and (d) developing professionalism in a sustainable way by taking reflective action categorized fairly enough.